Association between worldwide dietary and lifestyle patterns with total cholesterol concentrations and DALYs for infectious and cardiovascular diseases: An ecological analysis. Issue 4 (December 2015) - Oggioni, C.; Cena, H.; Wells, J.C.K.; Lara, J.; Celis-Morales, C.; Siervo, M.
Abstract: Global dietary and lifestyle trends are primary risk factors for communicable and non-communicable diseases. An ecological analysis was conducted to examine the association of global dietary and lifestyle patterns with total cholesterol concentrations. This study also investigated whether total cholesterol modified the association between dietary and lifestyle habits with disability-adjusted-life-years-lost (DALYs) for infectious and cardiovascular diseases (CVDs). Country-specific mean total cholesterol concentrations and DALYs for infectious and CVDs were obtained. Data were then matched to country-specific food and energy availability for consumption and information on obesity, physical inactivity, urbanization, gross domestic product (GDP), life expectancy and smoking. Stepwise multiple regression models were developed to identify significant predictors of total cholesterol concentrations and DALYs for infectious and CVDs. Life expectancy and egg and meat consumption were significantly associated with cholesterol concentrations. DALYs for infectious diseases were associated with smoking, life expectancy and per capita GDP. Smoking was the only predictor of DALYs for CVDs. The improvement of socio-demographic conditions and economic growth is likely to reduce the burden of communicable diseases in developing countries. A concurring increase in non-communicable diseases is expected, and these results have, yet again, identified smoking as a primary risk factor for CVDs.